Golden zone storage assignment and picking performance: An empirical analysis of manual picker-to-parts OP systems in grocery retailing. Issue 10 (2022) - Loske, Dominic; Koreis, Jonas; Klumpp, Matthias
Abstract: Manual picker-to-parts order picking (OP) systems are usually laborious and cost-intensive. Nevertheless, they are still predominant in warehouse operations of traditional brick-and-mortar grocery retailers. Storage assignment strategies are highly relevant for the outcomes of OP systems. Aspiring to improve picking performance and worker health, the concept of golden zone storage assignment is frequently applied in practice. This assignment strategy includes the placing of high-demand stock-keeping units at the height between the picker's waist and shoulders. Although simulation approaches indicate a positive impact of golden zone storage on the outcomes of OP systems, empirical evidence remains scarce. Therefore, we test this assumption with an empirical setting, including 1, 570, 049 picks performed by 156 order pickers in one warehouse operated by a large German brick-and-mortar grocery retailer. We apply a log-logistic accelerated failure time model and incorporate human factors through a mixed-effects model allowing one regression line per order picker. Our findings offer counter-intuitive insights because we find that golden zone storage assignment decelerates the picking process by 2.55% compared to ground-level picks. From a managerial viewpoint, our findings highlight the conflicting relation of economic- and ergonomic-driven evaluations for labor-intensive OP systems. Results call for a more differentiated typology of golden zone storage, including the depth of rack picking locations.